Coarse-grained refractory composites based on Nb-Al2O3 and Ta-Al2O3 castables. Issue 14 (1st October 2018) - Zienert, Tilo; Farhani, Mahdi; Dudczig, Steffen; Aneziris, Christos G.
Abstract: Coarse-grained refractory composites, with grain sizes between 20 and 5000 µm, based on Nb-Al2 O3 and Ta-Al2 O3 castables were produced for the first time and characterised in terms of shrinkage after sintering, splitting tensile strength, compressive strength, porosity and the measurement of the elastic properties ( E, G and ν ). After sintering at a temperature of 1600 °C, the shrinkage of the composites was 1.5% and 0.3%. Measured values of splitting tensile strength were between 5.5 and 15 MPa and the ones of compressive strength were between 23 and 89 MPa. Values of E and G were between 117 and 45 GPa and 48–17 GPa, respectively, for samples with 11–45 vol% refractory metal. Poisson's ratio was found to be very sensitive to the bonding between the fine matrix and coarse-grained particles of the composites. Its value increased from 0.25 for good bonding to ν = 0.43 in case of poor bonding between the coarse metal particles and the fine ceramic matrix. DTA/TG measurement under air atmosphere showed that the metal-ceramic composites start to oxidise at temperatures above 450 °C.